PENGEMBANGAN KEMAMPUANSISWA MENELITI SEJARAH LOKAL MELALUI MODEL INKUIRI (Studi Kasus di SMA Negeri 5 Purwokerto) - Suwamo, Suwamo; Kartono, Kartono (Jurnal Cakrawala Pendidikan, 2016)
The purpose of this study is know effectivity of inquiry’s model in developing pupil’s ability studying local history at SMA Negeri 5 Purwokerto year of 2006 2007. This study is a classroom action research with subject mailer of history and topic about principles historical research. There are four phase in this classroom actiOn research, i.e.: planning, classroom action, observation and reflection. The result of this study shows that inquiry’S model effective enough to developing pupil’s ability in studying local history. There is significant improving in instructional process of historical subject matter by inquiry’s model from first cydies toward third cyclies. The significan, improving could be seen by pretest and POSllest values in every cyclies, angket value in first cyclies, and collective’s duties from first cyclies toward third cyclies